Sustainability transitions and their relationship to digital technology - Alamoodi A.H.; Albahri O.S.; Albahri A.S.; Mohamad Sharaf I. (Elsevier, 2025)
In this chapter, we will define about sustainability transitions and their relationship with digital technology (DT), definitions, and concepts of DT, DT process, and business models. ? 2024 Elsevier Inc. All rights reserved.